The Evaluation of Animal Models in the Development of Anticancer Agents: From Preclinical to Clinical Tests - Wang, Jie; Dong, Haiyan; Liu, Jian; Zheng, Ning; Xie, Xiaodong; Jia, Lee (Current Cancer Drug Targets, 2019)
Background: One of the main reasons for most of the anticancer drugs to fail in the late preclinical testing and early clinical trials is the differences in drug effects observed from animals and patients, and the challenge has been to find a balance to reduce the inherent differences from species. Objective: Predicting safe starting doses and dosing schedules for human clinical trials is the main purpose of toxicological studies of anticancer drugs. Methods: Relevant information and data were assimilated from manuscripts, congress publications, and online sources. Results: We systematically overview the cons and pros of animal models and briefed the ways to determine human clinical starting doses derived from animal toxicological studies for anticancer drugs. Conclusion: This information helps smart select the suitable predictive model for anti-cancer drugs with the different mechanisms and emphasized the pharmaceutical challenges behind and ahead.
Keywords: starting doses